Revisiting rice breeding methods – evaluating the use of rapid generation advance (RGA) for routine rice breeding - Collard, Bertrand C. Y.; Beredo, Joseph C.; Lenaerts, Bert; Mendoza, Rhulyx; Santelices, Ronald; Lopena, Vitaliano; Verdeprado, Holden; Raghavan, Chitra; Gregorio, Glenn B.; Vial, Leigh; Demont, Matty; Biswas, Partha S.; et al. (Informa UK Limited, 2017)
Rice production needs to increase in the future in order to meet increasing demands. The development of new improved and higher yielding varieties more quickly will be needed to meet this demand. However, most rice breeding programmes in the world have not changed in several decades. In this article, we revisit the evidence in favour of using rapid generation advance (RGA) as a routine breeding method. We describe preliminary activities at the International Rice Research Institute (IRRI) to re-establish RGA on a large scale as the main breeding method for irrigated rice breeding. We also describe experiences from the early adoption at the Bangladesh Rice Research Institute. Evaluation of RGA breeding lines at IRRI for yield, flowering time and plant height indicated transgressive segregation for all traits. Some RGA lines were also higher yielding than the check varieties. The cost advantages of using RGA compared to the pedigree method were also empirically determined by performing an economic analysis. This indicated that RGA is several times more cost effective and advantages will be realized after 1 year even if facilities need to be built. Based on our experience, and previous independent research empirically testing the RGA method in rice, we recommend that this method should be implemented for routine rice breeding in order to improve breeding efficiency